A interpretação "reflexiva" do pronome no português do Brasil - Galves, Charlotte (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2016)
The aim of this paper is to show that the possible "reflexive" interpretation of the pronoun ele in Mineiro dialect of Brazilian Portuguese (BP) - for example in (1) "João vê ele no espelho": "John sees himself in the mirror" - is not relatable, in this dialect, to its character of anaphora, in the sense of Chomsky (1981), as claimed by Lemle (1984). I claim that it remains a pronoun and I show that in other dialects of BP that do not allow (1), the reflexive interpretation of the pronoun is available too, in sentences where the apparent violation of Chomsky’s Binding Principle B is weaker than in (1). The behavior of the pronoun ele in BP is related to the fact that this language is "discourse-oriented", the pronoun being bound by the topic, which can also be the subject. I arque that there is no violation of Principle B because the possible co-reference between the object pronoun and the subject in (1) is not a relation of dependency. My analysis, therefore, supports Higginbotham’s "linking" analysis of binding. Further comments about ele in BP are related to the Overt Pronoun Constraint proposed by Montalbetti (1984)